Symmetrical synergy of hybrid Co9S8-MoSx electrocatalysts for hydrogen evolution reaction. (February 2017) - Zhou, Xiaofeng; Yang, Xiulin; Hedhili, Mohamed Nejib; Li, Henan; Min, Shixiong; Ming, Jun; Huang, Kuo-Wei; Zhang, Wenjing; Li, Lain-Jong
Abstract: There exists a strong demand to replace expensive noble metal catalysts with efficient and earth-abundant catalysts for hydrogen evolution reaction (HER). Recently the Co- and Mo-based sulfides such as CoS2, Co9 S8, and MoSx have been considered as several promising HER candidates. Here, a highly active and stable hybrid electrocatalyst 3D flower-like hierarchical Co9 S8 nanosheets incorporated with MoSx has been developed via a one-step sulfurization method. Since the amounts of Co9 S8 and MoSx are easily adjustable, we verify that small amounts of MoSx promotes the HER activity of Co9 S8, and vise versa. In other words, we validate that symmetric synergy for HER in the Co- and Mo-based sulfide hybrid catalysts, a long-standing question requiring clear experimental proofs. Meanwhile, the best electrocatalyst Co9 S8 -30@MoSx /CC in this study exhibits excellent HER performance with an overpotential of −98 mV at −10 mA/cm 2, a small Tafel slope of 64.8 mV/dec, and prominent electrochemical stability. Graphical abstract: Highlights: It is the first report to prepare Co9 S8 by electrochemical deposition strategy. Strong electron transfer from Co to Mo via the S atoms was verified by XPS results. We firstly validated symmetric synergy for HER between Co- and Mo-based catalysts. The best HER records for Co9 S8 -based catalysts were obtained in this study.